2010
DOI: 10.1002/chem.200902728
|View full text |Cite
|
Sign up to set email alerts
|

On the Mechanism of Action of Fullerene Derivatives in Superoxide Dismutation

Abstract: We have studied the mechanism of the antioxidant activity of C(60) derivatives at the BP86/TZP level with inclusion of solvent effects (DMSO) by using the COSMO approach. The reaction studied here involves degradation of the biologically relevant superoxide radical (O(2)(*-)), which is linked to tissue damage in several human disorders. Several fullerene derivatives have experimentally been shown to be protective in cell culture and animal models of injury, but precisely how these compounds protect biological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
30
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(31 citation statements)
references
References 55 publications
1
30
0
Order By: Relevance
“…Previous studies have shown that the radical-scavenging abilities of C 60 (OH) 24 have been attributed to the molecular properties of fullerenols, including large electron affinity and formation of electron-deficient areas on the C 60 , 13 and these properties of C 60 (OH) 24 may lead to direct ROS scavenging similar to that catalyzed by superoxide dismutase. 15,46 However, in the present study, our results have clearly indicated that C 60 (OH) 24 protects against H 2 O 2 -induced cell death through activation of Nrf2/ARE signaling and induction of phase II antioxidant enzymes such as HO-1, γ-GCS, and NQO-1, thus providing an insight into mechanisms by which C 60 derivatives exert protective effects against cell death induced by oxidative stress.…”
mentioning
confidence: 41%
“…Previous studies have shown that the radical-scavenging abilities of C 60 (OH) 24 have been attributed to the molecular properties of fullerenols, including large electron affinity and formation of electron-deficient areas on the C 60 , 13 and these properties of C 60 (OH) 24 may lead to direct ROS scavenging similar to that catalyzed by superoxide dismutase. 15,46 However, in the present study, our results have clearly indicated that C 60 (OH) 24 protects against H 2 O 2 -induced cell death through activation of Nrf2/ARE signaling and induction of phase II antioxidant enzymes such as HO-1, γ-GCS, and NQO-1, thus providing an insight into mechanisms by which C 60 derivatives exert protective effects against cell death induced by oxidative stress.…”
mentioning
confidence: 41%
“…The mechanism of O 2 Á À quenching is similar to that of the quenching of superoxide dismutase. [51][52][53] The radical easily binds to the electron-deficient area of the fullerene surface, resulting in electron transfer to the fullerene cage. Then, the binding of a second superoxide radical anion to an adjacent electron-deficient position induces the destruction of O 2 Á À , production of hydrogen peroxide and regeneration of the original fullerene.…”
Section: Ros-scavenging Property Of Fullerenesmentioning
confidence: 99%
“…For instance, C 70 and their derivatives exhibited higher photodynamic therapy and antioxidation efficiency due to the much more extended conjugated π-system of the cage, which can efficiently absorb electrons. [8][9][10][11][12] Metallofullerenes of larger carbon cages (e.g. Gd@C 82 and Gd@C 82 (OH) x ) also showed promises as radiotracers, magnetic resonance imaging (MRI) contrast reagents and anticancer drug with high-efficacy and low-toxicity.…”
Section: Introductionmentioning
confidence: 99%